2021
DOI: 10.3390/sports9090125
|View full text |Cite
|
Sign up to set email alerts
|

Prescription and Effects of Strength Training in Individuals with Intellectual Disability—A Systematic Review

Abstract: The practice of physical exercise (PE), especially strength training (ST), has health benefits in the healthy population; however, the literature is scarce in the recommendations related to the population with intellectual disability (ID). This study represents the first analysis on the topic and aims to examine the structure and efficacy of ST experimental intervention programs in individuals with ID. This systematic review was carried out between January and April 2021, using the PubMed, Web of Science, Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Furthermore, it has been shown that the practice of PA has social benefits as it favours inclusion and social relation [9,10]. As well as the psychological and social benefits, some researchers [11,12] state that the practice of PA by people with a disability also provokes physical benefits such as better fitness, the ability to execute movements and functionality permitting greater autonomy and self-sufficiency. Bearing in mind that it has been said that the practice of PA benefits this population both in their physical and mental health [13], it is necessary for them to have adequate levels of PA practice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that the practice of PA has social benefits as it favours inclusion and social relation [9,10]. As well as the psychological and social benefits, some researchers [11,12] state that the practice of PA by people with a disability also provokes physical benefits such as better fitness, the ability to execute movements and functionality permitting greater autonomy and self-sufficiency. Bearing in mind that it has been said that the practice of PA benefits this population both in their physical and mental health [13], it is necessary for them to have adequate levels of PA practice.…”
Section: Introductionmentioning
confidence: 99%
“…The literature recommends that exercises selected be simple and easy to understand for PLWD. In addition, exercise leaders should have a personalized follow-up to instruct and demonstrate each exercise in different ways so that the practitioner can verify if the individual can perform it correctly ( Duplanty et al, 2014 ; Jacinto et al, 2021 ). Therefore, a period of familiarization with the exercises is essential for individuals with DS to learn the proper execution of the movement, eliminate the fear of using the equipment and perform the movement so that there are positive effects of the RT ( Duplanty et al, 2014 ; Jacinto et al, 2021 ).…”
Section: Evidence For Prescribing Resistance Training In Individuals ...mentioning
confidence: 99%
“…These results are promising considering that individuals with DS have a higher incidence of cardiovascular risk factors such as low cardiorespiratory capacity, loss of muscle strength and obesity ( Hu et al, 2013 ). Thus, numerous studies have demonstrated the beneficial effects of physical exercise that result in improving cardiopulmonary capacity, strength and body composition, and consequently improves cardiovascular parameters ( González-Agüero et al, 2011b ; Fernhall et al, 2013 ; Wee et al, 2015 ; Sugimoto et al, 2016 ; Jacinto et al, 2021 ).…”
Section: Health and Potential Benefits Of Rt In Individuals With Down...mentioning
confidence: 99%
“…According to the norms in the guidelines on exercise testing and exercise prescription issued by the American Sports Medical Association (ACSM), the exercise frequency, exercise intensity, exercise time, exercise form, exercise volume, and the progressive rate are regarded as the golden criteria of the fitness industry (frequency, intensity, time, and type [FITT]-VP). At the same time, they are also recognized by many scholars at home and abroad and serve as the basic criteria for people with intellectual disabilities to formulate exercise prescriptions (11,12). Therefore, this paper has taken people with intellectual disabilities as an example, reviewed the current situation of their physical fitness, systematically reviewed the literature related to the intervention of exercise prescription to promote the healthy physical fitness of people with intellectual disabilities, found out the advantages and disadvantages, and then provided a theoretical and practical reference for improving the prescription design.…”
Section: Introductionmentioning
confidence: 99%